Prevalence of post-partum genital tract infections in the mother and selected neonatal infections in rural Bangladesh - Gazi, Rukhsana; Chowdhury, AMR; Mahmud, Shah Noor; Karim, Fazlul (BRAC Research and Evaluation Division (RED), 2019)
The present study was designed to estimate the prevalence of post-partum infection and two neonatal infections in rural Bangladesh and to identify the factors and determinants related to these infections. In this study, a total of 400 women (200 from WHOP area and 200 from comparison area) were interviewed retrospectively through structured questionnaire. In general, the prevalence of post-partum infection and selected neonatal infection were lower in WH 0 P area than those of the comparison area. But the difference in prevalence rates between the program and comparison areas were not statistically significant. Again, the presence of trained TBAs during delivery could not provide beneficial effect in the outcome of post-partum infection in the program' area. In the program area, the mothers were still found to be using indigenous materials on cord of the neonates. Although, the results were less conclusive due to small number of samples, the delivery complications (prolonged labour, leaking membrane etc.) and the cultural factors such as using unclean water for washing the materials used as vaginal pads found to be associated with increased risk of post-partum infection.